Closed circuitry operation influence on microbial electrofermentation: Proton/electron effluxes on electro-fuels productivity. (November 2015) - Nikhil, G.N.; Venkata Subhash, G.; Yeruva, Dileep Kumar; Venkata Mohan, S.
Highlights: Novel hybrid reactor for harnessing bioelectricity and biohydrogen simultaneously. System buffering was critical factor during acidogenic–electrogenic processes. Influence of external resistance over anode potential. Voltammograms of closed circuitry operation deciphered electron delivery. Abstract: A novel biocatalyzed electrofermentor (BEF) was designed which uncovers the intricate role of biocatalyst involved in cogeneration of electro-fuels (hydrogen and electricity). The specific role of external resistance ( R ext, electrical load) on the performance of BEF was evaluated. Four BEFs were operated separately with different resistances (25, 50, 100 and 200 Ω) at an organic load of 5 g/L. Among the tested conditions, external resistance ( R 3 ) with 100 Ω revealed maximum power and cumulative H2 production (148 mW and 450 mL, respectively). The competence of closed circuitry comparatively excelled because it facilitates congenial ambiance for the enriched EAB (electroactive bacteria) resulting high rate of metabolic activity that paves way for higher substrate degradation and electro-fuel productivity. Probing of electron kinetics was studied using voltammetric analyses wherein electron transfer by redox proteins was noticed. The designed BEF is found to be sustainable system for harnessing renewable energy through wastewater treatment.